THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION OF PENSION SAVING BANK NATIONAL (BTPN) BRANCH SUNGGUMINASA - Wahyudi; Dian Parawansa; Fahrina Mustafa (Scientia Integritas Utama, 2023)
The National Pension Savings Bank (BTPN) has come a long way, since it was founded in Bandung, West Java in 1958, and then changed its name in 1986 to become the National Pension Savings Bank. BTPN began being listed on the Jakarta Stock Exchange in 2008 and a year later added a financing business to micro business complements the pension banking service portfolio. Recognizing the current challenges, that companies are required to change the way they do business, we decided to take a step further, by creating and launching “Daya” in 2011. Based on the “Opportunity and Call” business philosophy, Daya present by offering an opportunity to all BTPN stakeholders to participate in the mission to empower millions of mass market in Indonesia. In the regression equation, there are 2 negative variables and 3 other positive variables, meaning that if the independent variable increases, the dependent variable decreases and if the independent variable decreases, the dependent variable also increases. Because there are several factors from the item of each variable that influence the assessment of service quality so that there is an asymmetric flow between the independent and dependent variables. From the results of the regression coefficients obtained, it shows that the direct evidence factor (b1 = 0.000) then responsiveness (b3 = 0.000) and assurance (b4 = 0.000) are the distribution factors that affect customer satisfaction, then reliability (b2 = 0.010), while empathy ( b5 = 0.723) is a factor that does not affect customer satisfaction at all.